Mechanical and physical properties of cassava starch-gelatin composite films - Tongdeesoontorn W. (2014)
The effect of gelatin concentrations on the mechanical properties and solubility of cassava starch-based films containing glycerol was studied. Increasing concentration of gelatin increased tensile strength but reduced elongation at break and water solubility of the composite films. Films containing 30% gelatin showed the highest tensile strength. Fourier transform infrared spectroscopy (FT-IR) spectra indicated intermolecular interactions between cassava starch and gelatin in composite films. The X-ray diffraction (XRD) technique demonstrated pseudo-crystalline regions in the cassava starch-gelatin composite films, and it is supposed that the interactions between cassava starch and gelatin were shown in the diffractograms by shifts in scattering angles. The differential scanning calorimetry (DSC) thermograms and scanning electron microscopy (SEM) micrographs confirmed homogeneity of cassava starch-gelatin films. Cassava starch-gelatin composite films have the potential to replace conventional packaging, and the films developed in this work are suggested to be suitable for low-moisture food and pharmaceutical products. © 2012 Taylor and Francis Group, LLC.